Convenient synthesis of substituted benzo[e][1, 2, 4]- or [d][1, 2, 6]oxadiazepines, benzo[f][1, 3, 5]triazocines from N-aryliminoesters. Issue 11 (16th March 2017) - Saied, Tarak; Jelaiel, Nourchaine; Efrit, Mohamed Lotfi; Fort, Yves; Comoy, Corinne
Abstract: We report herein a short and efficient synthesis of benz[ e ][1, 2, 4]- or [ d ][1, 2, 6]oxadiazepines and benzo[ f ][1, 3, 5]triazocines from easily prepared N -aryl iminoesters. The strategy involves a bis-nucleophile reagent (hydroxylamine or guanidine) that promotes a one-step ring closure from the starting functionalized iminoesters. Graphical abstract: